2021
DOI: 10.1108/rjta-12-2019-0060
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing and finishing of cotton fabric with eucalyptus leaves extracts

Abstract: Purpose The purpose of this study is to establish a suitable procedure for dyeing and multifunctional finishing on 100% cotton using extracts of eucalyptus leaves in an eco-friendly manner. Design/methodology/approach Box–Behnken design of experiments and analysis of variance (ANOVA) were used to optimise the conditions of extraction, dyeing and finishing. Phytochemical analysis was performed to determine the chemical constituents of the extracts. Colour strength, fastness properties were evaluated for dyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, this property decreased after 20 washing cycles. [ 38 , 39 ] Endris & Govindan, 2021, 2022 Cotton fabrics dyed with EG leaf extracts were meta-mordanted with aluminum sulfate and post-treated with EG essential oil. A yellow color was obtained in the samples and the optimized samples (dyed and treated) showed excellent K/S and very good color fastness to lighting, washing, and rubbing.…”
Section: Methodsmentioning
confidence: 99%
“…However, this property decreased after 20 washing cycles. [ 38 , 39 ] Endris & Govindan, 2021, 2022 Cotton fabrics dyed with EG leaf extracts were meta-mordanted with aluminum sulfate and post-treated with EG essential oil. A yellow color was obtained in the samples and the optimized samples (dyed and treated) showed excellent K/S and very good color fastness to lighting, washing, and rubbing.…”
Section: Methodsmentioning
confidence: 99%
“…when dyed with natural dyes such as eucalyptus leaves, peanut skins, and pomegranate peels. [1][2][3][4] However, the application of natural dyes has also some problems. One of the most important problems is the low dye absorption which necessitates the use of potentially toxic metal mordants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, textiles show functional properties such as antibacterial, ultraviolet (UV) protection, etc. when dyed with natural dyes such as eucalyptus leaves, peanut skins, and pomegranate peels 1–4 . However, the application of natural dyes has also some problems.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, it was reported that Euclea divinorum extract was a natural dyestuff that could be used for dyeing cotton 2 . In another study, it was reported that cotton fabrics can be dyed and multi‐finished in a single step using eucalyptus leaf extract 3 . In another study, it was stated that silk fabrics can be dyed in a microwave environment with tannin‐based extract obtained from coconut fibres 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 In another study, it was reported that cotton fabrics can be dyed and multi-finished in a single step using eucalyptus leaf extract. 3 In another study, it was stated that silk fabrics can be dyed in a microwave environment with tannin-based extract obtained from coconut fibres. 4 In another research, organic cotton fabrics can be dyed in a microwave environment using barbery, dyer's oak and dyer's oak plus barbery plants.…”
Section: Introductionmentioning
confidence: 99%